Psychotropic drug utilization in psychiatric outpatient department of a tertiary care government hospital - Jena, Pragyan Paramita; Naik, Birendra Narayan; Rath, Bhabagrahi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Mental disorders are associated with significant distress in social, occupational and other important activities. Of the ten health conditions contributing to the DALYs, four are psychiatric disorders. Psychiatric disorders form an important public health priority and major causes of morbidity. Psychotropic drugs had a remarkable impact in psychiatric practice. The utilization, clinical practice, effectiveness and safety in real life situation need continuous study. Methods: A cross-sectional study was carried out by analyzing prescriptions of patients who visited the OPD of the psychiatry department of VIMSAR, Burla for a period of 4 months. Patients of all ages and both sexes were included in this study with exclusion of patients suffering from epilepsy and cases with uncertain diagnosis. The prescribing pattern was analyzed using WHO basic drug indicators. Results: Average number of drugs per prescription was 3.17. Bipolar affective disorder (BPAD) was the most common psychiatric condition (44%) with a male predominance followed by schizophrenia. Olanzapine was the most common antipsychotic used. The most frequently used fixed dose combination was tri-hexiphenydyl and risperidone. Prescribing frequency of different psychotropic drugs (antipsychotics, antianxiety, selective serotonin reuptake inhibitors, tricyclic antidepressant, mood stabilizers) were compared. Conclusions: The study advocated a rational use of psychotropic drugs with fewer deviations due to socio-economic status of patients and prescription practices of healthcare providers.